Patterns of Protestant Ethics and Modern Culture in Greta Thunberg’s Public Appearances - Hintz, Marcin (Journal for the study of religions and ideologies, 2020)
The 16 year old Swedish girl from Stockholm in the year 2019 was created by media as a suitable candidate for the Nobel Peace Prize and recognized as one of the most influential people of the year 2019. Her ecological message focusing on global climate changes is one of the most exciting phenomena in socio-political life in the European context of the second decade of the 21st century. She grew up in influential, artistic but also a typical Swedish family, deeply rooted in the Swedish tradition. Greta becomes a symbol of the climatological movement; she arranges a climate protest called School strike for climate, Fridays for Climate or Fridays for Future (FFF). The article describes the Lutheran patterns and the roots of Greta Thunberg’s ecological activity. We analyze the imagery tied to her public appearances and interpret the analysis with a protestant ideology in the background. First, we try to understand why Greta Thunberg is sometimes called a prophetess: even the prime archbishop of Sweden Antje Jeckelen called her attitude prophetic. We will argue that there are some traces of apocalyptic imagery and rhetoric behind her statements. We compare them with some public appearances of her parents Malena Ernman and Svante Thunberg as well as Naomi Klein. Then we trace the family background of Greta which is rooted in Swedish patterns of the Protestant ”vita activa”. The last part is a review of the criticism of modernity present in the Greta’s speeches and writings as well as her parents’ writings. We will indicate some precedents in music and film framing this analysis with the musical family roots of 17-years old Greta.